Oncocytic pituicytoma in a patient with Cushing’s disease: a case report and narrative literature review - Li, Jing; Chen, Shuaiming; Tan, Huiwen; Yu, Yerong; Tang, Ying; Cai, Bowen; Li, Jianwei (Frontiers in Endocrinology, 2025)
BackgroundPosterior pituitary tumors (PPTs) are extremely rare, with fewer than 400 cases reported to date. In 2022, the World Health Organization (WHO) classified four types of tumors originating from the posterior pituitary: traditional pituicytoma, oncocytic pituicytoma, granular pituicytoma, and ependymal pituicytoma. To our knowledge, only one subject with coexistence of Cushing’s disease and oncocytic pituicytoma (spindle cell oncocytoma) has been reported, but the clinical features of this patient were not described in detail.Case presentationWe presented a case of a patient with Cushing’s syndrome and a pituitary mass. Transsphenoidal surgery was performed, and pathologic examination revealed two distinct tumors: a corticotroph adenoma with a diameter of less than 2 mm and a larger oncocytic pituicytoma. Post-surgery serum cortisol was 51 nmol/L, indicating complete remission. Corticotroph adenoma or corticotroph hyperplasia was identified after surgery in less than half of the subjects with Cushing’s disease and PPT.ConclusionsOur study indicates that Cushing’s disease in patients with PPT may be caused by the existence of collision lesions, with corticotroph adenoma or hyperplasia being difficult to detect due to their small dimensions.